2014
DOI: 10.4081/jlimnol.2014.768
|View full text |Cite
|
Sign up to set email alerts
|

Weather conditions influencing phosphorus concentration in the growing period in the large shallow Lake Peipsi (Estonia/Russia)

Abstract: The impact of water temperature (T), water level (L), photosynthetically active radiation (PAR), and wind speed (V) on the total phosphorus concentration (TP) in shallow eutrophic Lake Peipsi, the fourth largest lake in Europe, was studied. We used a long-term dataset

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(49 reference statements)
0
7
0
1
Order By: Relevance
“…Furthermore, several species of cyanobacteria are able to uptake and store bioavailable phosphorus, and thus the populations can sustain themselves on internal P storage [52]. Changes in the factors that regulate cyanobacteria abundance between early and late times of the growing season reported in the current study are most likely related to the changes in the relative importance of the sources of nutrient supply, as they are closely coupled to the seasonality of nutrient dynamics in Lake Peipsi [61,62]. Moreover, different cyanobacteria species may assimilate nutrients at different rates.…”
Section: Discussionmentioning
confidence: 68%
“…Furthermore, several species of cyanobacteria are able to uptake and store bioavailable phosphorus, and thus the populations can sustain themselves on internal P storage [52]. Changes in the factors that regulate cyanobacteria abundance between early and late times of the growing season reported in the current study are most likely related to the changes in the relative importance of the sources of nutrient supply, as they are closely coupled to the seasonality of nutrient dynamics in Lake Peipsi [61,62]. Moreover, different cyanobacteria species may assimilate nutrients at different rates.…”
Section: Discussionmentioning
confidence: 68%
“…TP showed a decreasing trend in two (August, October) of the three months in a three-month-data in Lake Peipsi s.s. that determined the overall trend in years 2001–2019. As in other shallow lakes (e.g., Søndergaard et al, 2003 , Nürnberg, 2009 ), increases in TP approaching autumn are explained by P release from sediments in Lake Peipsi (internal P load; Tammeorg et al, 2014 ). Earlier studies demonstrated that internal P load in Lake Peipsi correlates positively with water temperature in August and water level in months from August to October ( Tammeorg et al, 2020 ).…”
Section: Discussionmentioning
confidence: 70%
“…Выявлено влияние на концентрацию азота прибрежной растительности (Canham et al, 2012). На концентрацию общего фосфора в воде заметно влияют температура и уровень воды в озере, фотосинтетическая активность водных растений, ветер (Tammeorg et al, 2014).…”
Section: материал и методы исследованийunclassified